‘Only the murder accusations are missing’: A case study of antisemitism and anti-antisemitism in Gothenburg, 1849 - Carlesson Magalhães, Jens (Nordisk judaistik/Scandinavian Jewish Studies, 2023)
In 1848, the Götheborgs Dagblad newspaper was revived after a ten-year gap, and launched the anonymous submission column entitled ‘Anonyma Lådan’ (the Anonymous Box). In January and February 1849, many antisemitic letters and articles were published in the Swedish newspapers. Some letters defending Jews and Judaism were published in both ‘Anonyma Lådan’ and Göteborgs Handels- och Sjöfartstidning. Short of blood libel, the antisemitic side accused Jews of typical anti-Jewish stereotypes: for example, greed, hypocrisy and Jewish hatred of Christianity. Anti-antisemitic writers proclaimed a Christian identity that was based on humanism, stating that one could not be a true Christian if one attacked and hated Jews and Judaism. The Jewish congregation in Gothenburg and the society Judiska Intresset (The Jewish Cause) both chose a non-engaged approach to the antisemitic attacks in the newspaper, since it was not respectable to engage in such debates and, in their view, it would only cause more anti-Jewish sentiments if they did so. In this article, it is argued that the reasons behind the attacks were societal changes, but also, more importantly, that with ‘Anonyma Lådan’, antisemitic sentiments found a platform where such sentiments could be freely expressed.